KARAKTER MORFOLOGI DAN ANALISA DNA RAPD TANAMAN TUBA (Paraderris elliptica (Wall.) Adema)HASIL EKSPLORASIDI PROPINSI JAWA TIMUR - Sandra Wicaksono; Damanhuri Damanhuri; Darmawan Saptadi (Universitas Tribhuwana Tunggadewi, 2015)
The objective of the study was to determine the distribution of plants, morphologi plant characters and diversity of Tuba (Paraderris elliptica (Wall) Adema) as the results of explorationin the province of East Java. Exploration activities conducted by survey method (snowball sampling) based on the informationof